Persuasive Populism? Estimating the Effect of Populist Messages on Political Cynicism - Rooduijn, Matthijs; Brug, Wouter van der; Lange, Sarah L. de; Parlevliet, Jante (2017)
Abstract: Many European countries have seen a growth of populism in recent years. Extant research shows that populist parties are increasingly successful, and that populist messages appear more frequently in the media. This raises the question to what extent populist messages affect public opinion. The aim of this study is to assess whether populist messages fuel political cynicism by arguing that an arrogant, selfish and complacent political elite does not listen to what ordinary people find important. Moreover, it assesses whether populist messages affect only those already favourably predisposed towards populist parties, or whether it affects citizens across the board. The results of a survey experiment, conducted in the Netherlands, suggests that individuals who are exposed to populist messages are indeed more cynical afterwards than individuals who are exposed to a very similar, but more 'neutrally formulated' message. However, the effects seem to be restricted to supporters of populist